2021
DOI: 10.1111/bjh.18001
|View full text |Cite
|
Sign up to set email alerts
|

Durable humoral responses after the second anti‐SARS‐CoV‐2 vaccine dose in chronic myeloid leukaemia patients on tyrosine kinase inhibitors

Abstract: The COVID-19 pandemic is a serious healthcare challenge, leading to more than 5 million deaths worldwide so far. The rapid advent of modern messenger RNA-and adenovirus DNA vector-based anti-SARS-CoV-2 vaccines has already been associated with a significant reduction in the rate of COVID-19 deaths. 1 Haematological malignancies and/or their treatments are linked to impaired immunocompetence, which has been highlighted by recent reports of severe COVID-19 outcomes 2 and poor responses to SARS-CoV-2 vaccines. 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
(18 reference statements)
2
15
0
Order By: Relevance
“…We also studied the association between TKI therapy and anti-spike IgG levels in CML patients. In accordance with literature, all CML patients have demonstrated to have a good serological response ( 16 , 17 ). We observed levels of antibodies greater in patients who had received second- and third-generation TKI than in patients who had used imatinib (11,301 vs .…”
Section: Resultssupporting
confidence: 88%
“…We also studied the association between TKI therapy and anti-spike IgG levels in CML patients. In accordance with literature, all CML patients have demonstrated to have a good serological response ( 16 , 17 ). We observed levels of antibodies greater in patients who had received second- and third-generation TKI than in patients who had used imatinib (11,301 vs .…”
Section: Resultssupporting
confidence: 88%
“…Conversely, Claudiani et al. ( 25 ) found statistically insignificant differences in antibody titers between CML patients and healthy controls in their analysis.…”
Section: Resultsmentioning
confidence: 82%
“…malignancies and healthy controls (207.5 U/mL vs. 1078 U/mL). Conversely, Claudiani et al(25) found statistically insignificant differences in antibody titers between CML patients and healthy controls in their analysis.Other studies also mentioned the median antibody titers between subgroups of their cohorts. Active treatment of patients in a study byPerry et al (26) achieved lower antibodies when compared with treatment naive patients, although they were still lower compared to the healthy controls (13.7 U/mL, 1008 U/mL, and 1332 U/mL, respectively).…”
mentioning
confidence: 82%
“…Differences of age, screening practices, applied preventive methods for avoiding COVID-19 transmission, ethnicity, and comorbidities may be among the variables responsible from the discordance of mortality rates between studies. The COVID-19 vaccines were also studied in CML-CP and demonstrated robust immunologic activity in both humoral ( 8 ) and cellular ( 9 ) components following vaccination, dismissing concerns for impaired vaccine efficacy. Overall, the reviews concerning the issues mentioned above leave the impression that the presence of CML-CP was probably not a significant independent risk factor for severe COVID-19 or vaccine failure ( 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%